The effect of carbon and nickel additions on the precursor synthesis of Cr3C2-Ni nanopowder. Issue 8 (1st June 2018) - Kaunisto, Kimmo; Kotilainen, Minna; Karhu, Marjaana; Lagerbom, Juha; Vuorinen, Tommi; Honkanen, Mari; Vippola, Minnamari; Turunen, Erja
Abstract: Decreasing crystal size to nanoscale is a proven method to enhance material properties. In this study, nanosize Cr3 C2 and Cr3 C2 -Ni were synthetized and the reaction sequence was studied. Aqueous precursors using only water-soluble raw materials with varying carbon contents and a nickel addition were spray-dried. Glycine was used as a carbon source and chromium acetate hydroxide as a chromium source in the precursor solutions. Nickel nitrate hexahydrate was introduced as a nickel source to yield a metallic binder into the carbide nanopowder. Resulting powders were heat-treating to identify an applicable precursor composition producing the targeted Cr3 C2 phase with crystal size of tens of nanometers. Thermal synthesis tests of the precursor powders to yield Cr3 C2 took place at a temperature between 900 and 1300 °C under an Argon atmosphere. The synthesis of nanosize Cr3 C2 -Ni powder was successful at 1000 °C in 30 min, in a case of the best precursor. In order to produce the carbide phase with no residual oxide traces, relative carbon load has to be 48 wt%, while the stoichiometric amount of carbon in Cr3 C2 is 13 wt%. When also introducing the nickel source into the precursor, an even higher carbon load was required. The carbon surplus needed to enable the Cr3 C2 synthesis attributes to the non-homogeneity of the precursor composition. The chemical synthesis starting from water-soluble raw materials is a promising way of preparing nanosize Cr3 C2 -Ni with the targeted phase configuration.